Marketing Communication Tresna Art Bangkalan Melalui Instagram - Nur Intan Komariyah; Nadya Poernamasari (Journal of Social, Culture, and Language, 2023)
Madurese written batik has not received much attention from the outside community. Tresna Art is here as a pioneer in imaging Madurese Written Batik, here to showcase the beauty of Madurese Written Batik through social media Instagram Tresna Art Bangkalan in the digital era. Instagram is an effective social media platform for implementing marketing communication strategies. This research aims to determine the use of Tresna Art social media as a means of marketing communication and determine the optimization of social media at Tresna Art Bangkalan as a means of marketing communication in the digital era. This research uses a qualitative descriptive method, using New Media theory It is hoped that this research can solve problems regarding the topic studied, and can provide suggestions as material for assessing Tresna Art in optimizing social media as a marketing tool. Keywords: Madura Written Batik, Instagram Social Media, marketing communications